MANUSIA SEBAGAI CITRA ALLAH (Refleksi Teologis Biblis atas Kitab Kejadian) - Dhani Driantoro Gregorius (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Humans are God's creation. He configured to God himself and growing along with the world. In effect, man is the image of God which was given the mandate to rule the earth and set its future. The Fathers ofthe Council's own document on human KV II asserts that man is created in God's image with the ability to know and love his creator God.